Novel Aspects in Freshwater Fauna Conservation - Zoran Marinović; Simona Đuretanović (Diversity)
Freshwater ecosystems, which include rivers, lakes, wetlands, springs, streams, and ponds, harbor a rich diversity of life, making them some of the most biologically productive environments on Earth [...]